Large-scale Transformations of Socio-economic Institutions - Esther Ademmer; Joscha Beckmann; Rainer Schweickert (WWWforEurope, 2014)
We explain economic growth by both politics, i.e. government activity including spending as well as regulation, and institutional quality and its interaction with politics. This extends previous work on institution building in transition by looking at its impact and, at the same time, considering endogeneity problems. While intially planned in two stages, the modified approach is able to integrate the arguments developed in the cluster approach on varieties of capitalism and their potential explanatory power for economic growth. As forseen for the second stage, we estimate the determinants of transition based on the exogenous components of institution building only as well as on other factors, especially welfare policies. This approach also allows to integrate various measures of income or well-being as soon as panel data becomes available.
Keywords: F15; H50; P10; P20; 330; Economic strategy; Institutional reforms; Political economy of policy reform